Penggunaan Media dalam Pembelajaran Tematik Terpadu di MI NW Repok Are - Susanti, Yuliana (Lembaga Yasin AlSys, 2022)
This study aims to provide an understanding of the importance of using media in integrated thematic learning in Class II MI NW Repok Are Academic Year 2021/2022. This type of research is descriptive qualitative research. Data collection techniques in this study used Observation, Interview, Documentation, and Triangulation / Combined techniques and this data collection technique was through: interview sheets, observation sheets, student activity sheets, observation sheets of student learning activities and teacher observation sheets. The results of the study show that the media plays an important role in the teaching and learning process, especially in integrated thematic learning. Media that is made as well as possible will make students more interested in learning. Learning media can also facilitate the delivery of material and support the continuity of thematic learning, especially for second grade students at the Madrasah Ibtidaiyah level. Data analysis in this study is data codification, data presentation, and drawing conclusions. Based on data analysis, data was obtained that through the use of media in thematic learning it was easier for teachers to carry out their roles as facilitators, models and role models, educators, and supervisors. In addition, learning outcomes, interest and student learning motivation are also increasing